Analisis Cemaran Bakteri Pada Bubur Sumsum yang dijual di Pasar Pasalaran Cirebon - Solikhah Solikhah; Pipin Supenah; Usdiyanto Usdiyanto; Al Rissajati Fatihah (Jurnal Anestesi, 2023)
In Indonesia, foodborne disease is still a food safety issue. Bubur sumsum or jenang sumsum is a porridge made from rice flour processed with coconut milk and brown sugar. Testing a food to determine whether it is suitable for consumption, one of which uses the approach of the number of microbes contained in food products. One of them is the Total Plate Number (ALT) method. The Total Plate Numbers (ALT) method is widely used for calculating the number of microbes in products that show the quality of contamination and hygiene of a product during the production process. This study aims to determine the value of microbial contamination numbers in marrow porridge sold at Pasar Pasalaran Cirebon, determine the marrow porridge that does not meet the requirements of BPOM RI regulation No. 13 of 2019 regarding the maximum limit of microbial contamination of food, and determine the percentage of marrow porridge that does not meet the requirements of BPOM RI regulation No. 13 of 2019 regarding the maximum limit of microbial contamination of processed food sold at Pasar Pasalaran Cirebon. This research method is descriptive quantitative while the examination is by the total plate number of bacteria method. Sampling was done by accidental sampling method. The samples of this study were 5 samples of marrow porridge sold in Cirebon Pasalaran Market with the weight of each sample of 10 grams. Based on the results of the study, the value of Total Bacterial Plate Numbers in marrow porridge sold in Pasar Pasalaran Cirebon Regency was the highest at 3.8 x 105 colonies / g and the lowest at 2.5 x 103 colonies / g. There were 3 samples of marrow porridge sold in Pasar Pasalaran Cirebon Regency. There are 3 samples of marrow porridge that do not meet the requirements of BPOM RI regulation No.13 of 2019, namely samples A, D, and E. It can be concluded that the total bacterial plate number test on 5 samples of marrow porridge sold at the Cirebon Pasalan Market shows that 60% or 3 samples of marrow porridge do not meet the requirements of BPOM RI No.13 of 2019.